Citizenship and democracy beyond the nation-state? - Glalp, Haldun (SAGE PUBLICATIONS LTD, 2013)
This article surveys the evolution of the field of citizenship and democracy beyond the stages identified by T. H. Marshall, through globalization and the weakening of the welfare function of the nation-state. Globalization has led to two distinct issue areas: the rise of identity claims as part of democratic demands and the regulation of human rights by supranational institutions. This article critically examines the pros and cons of the notion of group rights as a response to multiculturalist demands and considers the context within which a global democracy may be envisioned. This article concludes with a brief discussion of several pressing questions raised in the recent literature with regard to these two areas.
Keywords: Citizenship; democracy; globalization; identity; nation-state; CIVIL-SOCIETY; POSTMODERNISM; POLITICS; Social Sciences - Other Topics